Early diagnosis of myocardial fibrosis in patients with epicardial obesity - O. V. Gritsenko; G. A. Chumakova; E. V. Trubina (Российский кардиологический журнал)
It has been proven that about half of patients with heart failure (HF) have a preserved the left ventricle (LV) ejection fraction (EF), which complicates early detection of HF. Currently, there is a search for non-invasive methods for diagnosing myocardial fibrosis at the preclinical heart failure to prevent its progression and the appearance of clinical symptoms.Aim. To study the relationship of LV mechanics with the level of serum myocardial fibrosis markers in patients with epicardial obesity (EO).Material and methods. The study included 110 men with general obesity. Depending on echocardiographic data, the patients were divided into 2 groups: EO (+) with epicardial fat thickness (EFT) ≥7 mm (n=70); EO (-) with EFT <7 mm (n=40). All patients were studied for serum profibrotic markers (MMP-3, collagen I, collagen III, TGF-β, VEGFA, PICP) using enzyme-linked immunosorbent assay. Speckle-tracking echocardiography was used to study LV mechanics (LV twisting, LV twisting rate, time to peak twist, LV untwisting rate, time to peak untwist). The exclusion criteria were the presence of coronary artery disease, hypertension, type 2 diabetes.Results. In the group of patients with EO (+), a significant increase in the level of all studied profibrotic markers was revealed. According to the results of speckletracking echocardiography in the EO (+) group, an increase in the LV untwisting rate to -128,31 (-142,0; -118,0) deg/s-1 (p=0,002) and an increase in the time to peak untwist to 476,44 (510,0; 411,0) ms compared to the EO (-) group (p=0,03). A weak significant effect of EFT on LV untwisting rate was revealed in the EO (+) group (r=0,24; p=0,04). In addition, a significant relationship was found between the LV untwisting rate and markers of myocardial fibrosis: MMP-3 (r=0,21; p=0,04) and type III collagen (r=0,26; p=0,03).Conclusion. Thus, the obtained data suggest that patients with EO have signs of preclinical LV diastolic dysfunction, which are characterized by an increase in LV untwisting rate and level of serum profibrotic factors.